Clinical Characteristics and Metabolic Health Status of Obese Korean Children and Adolescents - Chun, Sunyoung (Korean J Fam Med, 2015)
BACKGROUND: This study aimed to determine the prevalence of metabolically healthy and unhealthy obesity (MHO and MUO, respectively) and examine the demographic, anthropometric, and lifestyle predictors of metabolic health status in Korean children and adolescents. METHODS: This study was based on data collected from the Korean Children-Adolescent Study in 2010. A total of 1,700 children (846 boys and 854 girls) were included in the primary cohort and classified into metabolically healthy and unhealthy groups according to factors related to the metabolic syndrome. Demographic and biochemical features were evaluated in study participants. Logistic regression estimated the odds ratios of having more fat mass among MUO compared with MHO children after adjusting for confounding factors. RESULTS: Mean body mass index was higher in the MUO group than in the MHO group (24.83 vs. 23.02 kg/m(2), respectively). The proportion of obese participants was also higher in the MUO group (59.4%) than in the MHO group (20.7%). MHO children were more likely to have parents with better socioeconomic status and a higher fruit and vegetable intake compared with MUO children. Higher fat mass and percent fat was associated with MUO according to multiple logistic regression analysis. CONCLUSION: Fat mass and percent fat are associated with metabolically healthy phenotypes of obesity among children and adolescents.